Determinants of Bank Credit in Indonesia (Universitas Negeri Semarang, 2022)
This study aims to determine and analyze the long-term and short-term effects of internal banking factors (CAR, LDR, NPL) and banking external factors (GDP, Inflation, Interest Rates, Money Supply, Industrial Production Index) on lending to commercial banks. The analytical method used is the Error Correction Model (ECM). The data used is time series data, which is compiled periodically in a monthly analysis from January 2014 to December 2020 in a time series. CAR and NPL have a significant negative effect on lending. In the short term, the LDR, GDP, Money Supply, and Industrial Production Index variables have a positive and significant effect on lending, while inflation and interest rates have no effect on lending in the short term, and lending has no effect on inflation, while the LDR, PDB, JUB, and IPI variables have a positive and significant effect on lending in the long term. And the reference interest rate variable has a positive and significant effect on lending in the long term. Penelitian ini bertujuan untuk menganalisis pengaruh dalam jangka panjang dan jangka pendek faktor internal (CAR, LDR, NPL) dan faktor eksternal (PDB, Inflasi, Suku Bunga Acuan, Jumlah Uang Beredar, Indeks Produksi Industri) perbankan terhadap penyaluran kredit pada bank umum di Indonesia. Metode analisis yang digunakan adalah analisis Error Correction Model (ECM). Data yang digunakan dalam penelitian adalah data time series bulanan dari Januari 2014 sampai dengan Desember 2020. Hasil penelitian menunjukkan dalam jangka pendek variabel CAR dan NPL berpengaruh negatif signifikan, variabel LDR, PDB, JUB, IPI berpengaruh positif dan signifikan serta inflasi dan suku bunga acuan tidak berpengaruh terhadap penyaluran kredit. Sedangkan dalam jangka panjang CAR dan inflasi tidak berpengaruh terhadap penyaluran kredit. Sedangkan variabel LDR, PDB, JUB, IPI berpengaruh positif dan signifikan terhadap penyaluran kredit dalam jangka panjang. Dan variabel suku bunga acuan berpengaruh positif dan signifikan terhadap penyaluran kredit dalam jangka panjang.